Contemporary Concise Review 2021: Interstitial lung disease. Issue 7 (5th May 2022) - McCarthy, Cormac; Keane, Michael P.
Abstract: The last 2 years have presented previously unforeseen challenges in pulmonary medicine. Despite the significant impact of the SARS‐CoV‐2 pandemic on patients, clinicians and communities, advances in the care and understanding of interstitial lung disease (ILD) continued unabated. Recent studies have led to improved guidelines, better understanding of the role for antifibrotics in fibrosing ILDs, prognostic indicators and novel biomarkers. In this concise contemporary review, we summarize many of the important studies published in 2021, highlighting their relevance and impact to the management and knowledge of ILD.